Development Strategy for Destination Branding of Ponorogo Regency - Yurisma, Dhika Yuan; Erdiana, Setya Putri (Gorga : Jurnal Seni Rupa, 2024)
The importance of destination branding is becoming more evident in the competition among places that serve as tourist, business, and even residential locations. The image or perception formed is vital as it shapes the identity of a destination. Essentially, destination branding is an effort to build individual perceptions of a destination by promoting its potential and strengths, ultimately forming a unique identity for that place. Ponorogo known for its strong cultural heritage, has not yet attracted much attention from the general public as a tourist destination. This study aims to identify the factors influencing tourist visits through demand analysis and to analyze the mapping of tourism potential by inventorying human resources, natural resources, supporting infrastructure, local community lifestyle patterns, and the support of the local government of Ponorogo Regency in developing a destination branding strategy. The methodology in this research destination strategy. Data collection techniques involve observation, documentation and literature review, as well as interviews with government officials, tourists or visitors. The collected data will be analyzed to create a mind map used in the concept of destination branding strategy design. The result of this research on the strategy for developing destination branding for Ponorogo Regency is a brand guideline book, complete with examples of its implementation in various promotional media., offering recommendations to the local government of Ponorogo Regency to increase tourist visits.